2015
DOI: 10.1007/s00467-015-3135-1
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of polyols and sugars in children with chronic kidney disease

Abstract: We show that the excretion of polyols and sugars depends on eGFR, which warrants a cautious interpretation of the results in patients with CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Additionally, the predicted R 2 (0.9296) was also in reasonable agreement with the adjusted R 2 (0.9804), with a difference of less than 0.2 [39]. Therefore, the relationship between the predicted and experimental values of hydroxyl value (OHV) response was proven to have a high R 2 -value, which suggested that the experimental values fitted well with the predicted value [40]. In addition, the adequate precision demonstrated that a signal-to-noise ratio of greater than 4 is desirable [41].…”
Section: Optimisation Reaction Conditions By Response Surface Methodosupporting
confidence: 63%
See 1 more Smart Citation
“…Additionally, the predicted R 2 (0.9296) was also in reasonable agreement with the adjusted R 2 (0.9804), with a difference of less than 0.2 [39]. Therefore, the relationship between the predicted and experimental values of hydroxyl value (OHV) response was proven to have a high R 2 -value, which suggested that the experimental values fitted well with the predicted value [40]. In addition, the adequate precision demonstrated that a signal-to-noise ratio of greater than 4 is desirable [41].…”
Section: Optimisation Reaction Conditions By Response Surface Methodosupporting
confidence: 63%
“…Polyol is known to be a very important and beneficial material in pharmaceutical, food science and polymer chemistry [1][2][3]. Polyol is commonly used as raw materials in polymer chemistry in order to manufacture polyurethane products (coatings, elastomers and foam) by reacting with isocyanates [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with the present results, elevated levels of ribitol are associated with retinal cell apoptosis in DR. 36 Moreover, elevated levels of ribitol and myo-inositol in chronic kidney disease stages 3-5 have been reported. 37 …”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the present results, elevated levels of ribitol are associated with retinal cell apoptosis in DR (35). Moreover, elevated levels of ribitol and myo-inositol in chronic kidney disease stages 3-5 have been reported (36).…”
Section: Discussionmentioning
confidence: 99%